Pengembangan E-Katalog Berbasis Web untuk Digitalisasi Pemasaran Kerajinan Ulos dan Gorga Sumatera Utara pada UMKM - Dedi Leman; Maulia Rahman; Basorudin Basorudin (Riau Jurnal Teknik Informatika, 2026)
Traditional handicrafts such as ulos and gorga are important cultural assets of North Sumatra, yet the micro, small, and medium enterprises (MSMEs) that produce them still rely on conventional, face-to-face marketing that limits market reach and slows the regeneration of younger artisans. This study designs and builds a web-based electronic catalog (e-catalog) for ulos and gorga handicraft MSMEs to widen market access while preserving the cultural narrative behind each motif. The system was developed with the Waterfall method, covering requirement analysis, design, implementation, and testing. Requirements were gathered through interviews with three MSME partners and a review of related e-catalog studies. The system was built with the PHP CodeIgniter framework and a MySQL database, providing product catalog management, cultural-story content for each motif, an order-inquiry feature linked to WhatsApp, and an administrator dashboard. Black-box testing on 30 scenarios showed a 100% success rate, and a System Usability Scale (SUS) survey of 20 respondents produced an average score of 82.8, categorized as “Good to Excellent.” The e-catalog improves product visibility, shortens the distance between artisans and consumers, and supports preservation of ulos and gorga cultural knowledge alongside MSME economic empowerment. Specifically, the system strengthens the marketing competitiveness of partner MSMEs by replacing scattered, unstructured promotion through personal WhatsApp status and word of mouth with a single organized digital channel that presents product information and cultural narrative together, giving early indications of more effective and wider-reaching marketing communication for artisan groups that previously depended on face-to-face sales.